The association of maternal serum parameters with pregnancy induced hypertension in Chinese population - Yahui Li; Yun He; Qianqian Wang; Xueni Wang; Yongqiong Xie; Linbo Cheng; Haibo Yao (PLoS ONE, 2026)
Background Abnormal changes of peripheral blood parameters were observed in women with pregnancy induced hypertension (PIH) as indicators of multi-organ involvement, but the clinical significance of these promising biomarkers is still debated. This study aimed to determine the role of biochemical parameters and platelet indices for PIH identification and severity evaluation in Chinese population. Methods The clinical data of 837 singleton pregnant women were retrospectively analyzed and divided into normotensive control (n = 238), gestational hypertension (n = 213) and preeclampsia (n = 386) groups. Fasting blood samples were collected by first-time examination after admission for measurements by standard techniques. Multivariate logistic regression was performed to assess independent factors correlated with pregnancy induced hypertension. Receiver operating characteristic (ROC) curves were constructed to examine diagnostic accuracy. Correlation analysis was used to evaluate the association between these parameters and Apgar score and birth weight. Results The urea, creatinine (Cr), uric acid (UA), aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma-glutamyl transpeptidase (GGT), lactate dehydrogenase (LDH), mean platelet volume (MPV) and platelet distribution width (PDW) values in the gestational hypertension or preeclampsia groups were significantly higher than those in control group, while total protein (TP), albumin (ALB), prealbumin (PA) and platelet count (PLT) levels were significantly lower. In multivariate regression model, gestational age (GA), body mass index (BMI), UA, ALB, LDH and MPV were found to be independent factors associated with gestational hypertension and preeclampsia. ROC curve analysis indicated that UA, ALB and LDH had good diagnostic performance for preeclampsia with the areas under the curve (AUC) of more than 0.7. Conclusion UA, ALB, LDH and MPV have been identified as accessible and valuable biomarkers in diagnosis, severity assessment and prognosis evaluation for gestational hypertension and preeclampsia.